Cross-sectional serosurvey of Coxiella burnetii in healthy cattle and sheep from extensive grazing system in central Italy. (2020) - Barlozzari, G.; Sala, M.; Iacoponi, F.; Volpi, C.; Polinori, N.; Rombolà, P.; Vairo, F.; Macrì, G.; Scarpulla, M.
Abstract: A cross-sectional survey was carried out to estimate the seroprevalence of Coxiella burnetii in extensively grazed cattle and sheep from central Italy and to identify the related risk factors. Data on notified human Q fever cases in the area were also collected and described. A two-stage cluster sampling was performed. A total of 5083 animals (2210 cattle; 2873 sheep) belonging to 186 farms (92 herds; 94 flocks) were tested for the presence of antibodies against C. burnetii using a commercial enzyme-linked immunosorbent assay kit. The prevalence at the animal-level resulted three times higher in sheep compared to cattle (37.8% vs. 12.0%; χ 2 = 270.10, P < 0.001). The prevalence at the herd-level was also higher in sheep than in cattle (87.2% vs. 68.5%; χ 2 = 9.52, P < 0.01). The multivariate analysis showed a higher risk of seropositivity for cattle aged 67–107 months (OR 2.79, 95% CI 1.86–4.18), cattle >107 months of age (OR 2.07, 95% CI 1.36–3.14) and mixed breed cattle (OR 1.74, 95% CI 1.11–2.72). A herd size >92 animals was recognized as herd-level risk factor in cattle (OR 6.88, 95% CI 1.67–28.37). The risk of being seropositive was double in sheep belonging to flocks >600 animals (odds ratio (OR) 2.04, 95% CI 1.63–2.56). Sheep were confirmed to be the most exposed species. Nevertheless, the prevalence observed in cattle also suggests the potential involvement of this species in the circulation of the pathogen in the area. Seven confirmed human Q fever cases were reported. In five out of seven cases there was at least one exposed herd within a 5 km buffer. Even though the source of the infection was not identified, the possibility of C. burnetii circulating in the livestock and human population in the study area cannot be overlooked. The integration between veterinary and human surveillance will be crucial to understand the spread of this zoonosis and to support the adoption of appropriate control measures.